The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajpregu.00129.2015
|View full text |Cite
|
Sign up to set email alerts
|

Decreased excitability and voltage-gated sodium currents in aortic baroreceptor neurons contribute to the impairment of arterial baroreflex in cirrhotic rats

Abstract: Cardiovascular autonomic dysfunction, which is manifested by an impairment of the arterial baroreflex, is prevalent irrespective of etiology and contributes to the increased morbidity and mortality in cirrhotic patients. However, the cellular mechanisms that underlie the cirrhosis-impaired arterial baroreflex remain unknown. In the present study, we examined whether the cirrhosis-impaired arterial baroreflex is attributable to the dysfunction of aortic baroreceptor (AB) neurons. Biliary and nonbiliary cirrhoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…It has been reported that BDL-induced cirrhosis alters the expression level of ion channels such as voltage-dependent Na + channels ( Lee et al, 2016 ), epithelial Na + channels ( Kim et al, 2006 ), large-conductance K Ca (BK Ca ) channels ( Yuan et al, 2016 ; Jadeja et al, 2017 ), ATP-sensitive K + channels ( Yuan et al, 2016 ), transient receptor potential canonical subfamily (TRPC) channels ( Nedungadi and Cunningham, 2014 ; Jadeja et al, 2017 ), and transient receptor potential vanilloid subfamily (TRPV) channels ( Nedungadi et al, 2012 ; Belghiti et al, 2013 ; Hong-Qian Wang et al, 2019 ). In addition, we noted the downregulation of TMEM16A (and also TMEM16F) expression in cirrhotic BDL mice, but not in non-cirrhotic PPVL mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BDL-induced cirrhosis alters the expression level of ion channels such as voltage-dependent Na + channels ( Lee et al, 2016 ), epithelial Na + channels ( Kim et al, 2006 ), large-conductance K Ca (BK Ca ) channels ( Yuan et al, 2016 ; Jadeja et al, 2017 ), ATP-sensitive K + channels ( Yuan et al, 2016 ), transient receptor potential canonical subfamily (TRPC) channels ( Nedungadi and Cunningham, 2014 ; Jadeja et al, 2017 ), and transient receptor potential vanilloid subfamily (TRPV) channels ( Nedungadi et al, 2012 ; Belghiti et al, 2013 ; Hong-Qian Wang et al, 2019 ). In addition, we noted the downregulation of TMEM16A (and also TMEM16F) expression in cirrhotic BDL mice, but not in non-cirrhotic PPVL mice.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological function of the arterial baroreflex is to normally alter heart rate and blood pressure due to arterial wall tension changes. [4] Many evidences [4,15] have showed that the arterial baroreflex baroreceptors sensed the systemic blood pressure through baroreceptor terminals innervating aortic arch and carotid sinus, and then transmitted the arterial baroreceptor afferent discharge into the dorsal medial nucleus tractus solitarii. As a result, peripheral vascular resistance, heart rate, and arterial blood pressure were subsequently decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid and aortic baroreceptors sense the intraarterial blood pressure and modulate the sympathetic tone toward the opposite direction, that is, high blood pressure results in reduced sympathetic tone through baroreceptor activation, while enhanced sympathetic tone compensates for low blood pressure. [4]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted that sympathetic SGCs play critical roles in the physiological regulation of neuronal metabolism and survival, cell excitability, synaptic transmission, and overall sympathetic output [ 3 , 4 ]. Previous studies showed that certain pathological conditions including chronic heart failure [ 5 ], cirrhosis [ 6 ], and traumatic brain injury [ 7 ] cause autonomic imbalance due to sympathetic overactivity. However, the involvement of SGCs in the cellular mechanisms underlying abnormal sympathetic output remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%